In vivo study: black cumin extract (Nigella sativa) on antral follicle diameter and granulosa cell layer thickness as an effort to prevent infertility - Amalia, Amirul; Primindari, Risya Secha; Irawan, Dwi Dianita (MEDISAINS, 2024)
Background: Infertility is a health problem that affects approximately 10-15% of couples trying to achieve pregnancy worldwide. Various studies have shown that Nigella sativa (N. Sativa) has many health benefits, including reproductive health. However, studies examining the effectiveness of N. Sativa in preventing folliculogenesis disorders have never been reported.Purpose: This study aims to determine the benefits of administering N. Sativa in preventing folliculogenesis disorders as measured by the diameter of the antral follicles and the thickness of the granulosa cell layer.Methods: This research design uses an experiment with a randomized posttest-only controlled group design approach. There were 27 experimental animals (mice) divided into three groups, namely the negative control group (9 animals) and the positive control group (9 animals), as well as the treatment group (9 animals). The positive control group was exposed to two cigarettes of cigarette smoke per day. The treatment group was exposed to cigarette smoke and N. Sativa 300 mg/KgBW/day for 28 days. After that, the mice were sacrificed to take their ovaries. Then, the ovarian organ samples were stained with Hematoxylin-eosin and examined for the diameter of the antral follicles and the thickness of the granulosa cell layer in the antral follicles with photo slides at 400x magnification in 5 fields of view, statistical analysis using the Independent T-test.Results: There were significant differences in antral follicle diameter and granulosa cell thickness in mice exposed to cigarette smoke and N. Sativa. Administration of N. Sativa extract can increase granulosa cell thickness through estrogenic function. Administration of N. Sativa extract showed estrogenic activity by increasing serum estradiol levels. N. Sativa heterotrophic activity cannot be separated from the flavonoid and phenolic compounds contained in N. Sativa, which have been proven to have high estrogenic activity.Conclusion: N. Sativa extract is efficacious in improving the diameter of antral follicles and the thickness of granulosa cells caused by exposure to cigarettes.